2006
DOI: 10.1590/s1519-70772006000100008
|View full text |Cite
|
Sign up to set email alerts
|

Impacto de la aplicación del fair value en la volatilidad de la banca Brasileña: un estudio empírico

Abstract: En este paper es analizado el impacto que ha tenido la adopción del valor razonable sobre la volatilidad de los resultados y fondos propios en los bancos de Brasil. La muestra estuvo constituida por 73 bancos que representaban, a Junio del 2002, el 95,93% del total de activos del sistema nacional. Se realizo un análisis comparativo entre las volatilidades, con y sin los efectos de la nueva regulación, e se indago para conocer si existe algún síntoma de utilización de prácticas para el alisamiento de los benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
6

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 8 publications
1
3
0
6
Order By: Relevance
“…The statistical significance and the negative sign of the variable (NP-IncSEC) in explaining the IncSEC variable are consistent with the hypothesis of using income from securities for the purpose of income smoothing. This corroborates the findings of Zenderski (2005), Monteiro and Grateron (2006), Santos (2007), and Goulart (2007). A significant and inverse relationship between the explanatory variable and ΔEVA shows that banks use the classification of the availablefor-sale portfolio in these discretionary management actions.…”
Section: Identification Of Income Smoothing Using a One-stage Modelsupporting
confidence: 88%
See 3 more Smart Citations
“…The statistical significance and the negative sign of the variable (NP-IncSEC) in explaining the IncSEC variable are consistent with the hypothesis of using income from securities for the purpose of income smoothing. This corroborates the findings of Zenderski (2005), Monteiro and Grateron (2006), Santos (2007), and Goulart (2007). A significant and inverse relationship between the explanatory variable and ΔEVA shows that banks use the classification of the availablefor-sale portfolio in these discretionary management actions.…”
Section: Identification Of Income Smoothing Using a One-stage Modelsupporting
confidence: 88%
“…The authors concluded that managers of financial institutions use fair value adjustments as a method for practicing earnings management and for the management of equity levels. As a caveat, it should be noted that in the second stage, a positive relationship was observed between the discretionary portion of fair value adjustments and quarterly earnings, contrary to the evidence of income smoothing in the Brazilian market found by Zenderski (2005), Monteiro and Grateron (2006), Santos (2007), and Goulart (2007).…”
Section: Studies On the Use Of Securities For Earningsmentioning
confidence: 59%
See 2 more Smart Citations
“…Como contribuição ao avanço da literatura, o desenvolvimento do modelo de dois estágios para a identificação da discricionariedade da administração de instituições bancárias no processo de mensuração do valor justo dos derivativos possibilitou a constatação do uso dessa prática no gerenciamento de resultados. Estudos anteriores -como Ahmed et al (1997), Monteiro & Grateron (2006), Galdi & Pereira (2007) e Goulart (2007) -apresentaram evidências de utilização dos ganhos e perdas com derivativos com o alisamento de resultados em bancos, mas não associaram essas evidências a discricionariedade da administração, pelo fato de a metodologia utilizada não segregar essa parcela.…”
Section: Introductionunclassified